Pengaruh Motivasi Kerja Dan Tunjangan Kinerja Terhadap Kinerja Pegawai Man 1 Kota Serang - Desty Endrawati Subroto; Fidziah; Didi Wandi; Suhaemi (JURNAL ECONOMINA, 2024)
This study aims to examine the effect of work motivation on the performance of employees at MAN 1 Kota Serang. The specific objectives are: (1) to determine the effect of work motivation on employee performance, (2) to identify the effect of job allowances on employee performance, and (3) to analyse the combined effect of work motivation and job allowances on employee performance. The research applies a quantitative method, with data collected using research instruments and analysed statistically in order to test the proposed hypotheses. The sample used in this research is a population sample, as all members of the population were included, totalling 35 employees of MAN 1 Kota Serang. Data analysis techniques employed include product moment correlation analysis with a 5% significance level, as well as multiple regression analysis. The findings indicate that: (1) there is a positive and significant effect of work motivation on employee performance, with a t-value of 4.405 greater than the t-table value of 1.692; (2) there is a positive and significant effect of job allowances on employee performance, with a t-value of 4.504 greater than the t-table value of 1.692; and (3) work motivation and job allowances jointly have a positive and significant effect on employee performance, with an F-value of 10.933 greater than the F-table value of 3.28, and a significance level of 0.00 < 0.05.